The usefulness of big data in creating innovations. The example of Google Trends - Joanna Hernik (Managerial Economics)
A huge amount of data is collected by search engines. According to estimates, the Google search engine, which is dominant on the market, receives billions of search requests daily. Of particular note is that a large part of the collected data is available through the Google Trends service. As a consequence, various types of data can be used by enterprises for their development but they often do not take advantage of this opportunity. Therefore, the purpose of this article is to prove the suitability of the big data concept for creating and implementing product innovations, using the example of Google Trends. Discovering human needs and searching for answers to them is not only the domain of entrepreneurs, therefore this study may have a fairly broad practical applications. By adopting general assumptions, i.e. ones that do not refer to specific products or industries, the author has shown that the presented path may be recreated by both entrepreneurs and creators of political programs, as well as leaders of non-governmental organizations who need to implement innovations. The results revealed the selection of specific ways of entering queries in Google Trends and certain periods of analysis which are the most useful for creating innovations. Descriptive statistics (such as median) clearly show that the results typed in Google Trends are better when taken from a user perspective and can be used to create innovations. Despite substantial differences, the results do not allow for the conclusion that these differences were statistically significant. Thus, preliminary data supports the hypothesis, but more research is needed.